In Memoriam: Professor Ammar Siamwalla (1939–2025) - Leckcivilize, Attakrit; Bhula-or, Ruttiya (SOUTHEAST ASIAN JOURNAL OF ECONOMICS, 2025)
Professor Ammar Siamwalla, who passed away in October 2025 at the age of 86, was one of Thailand’s most influential economists. As a founding member and former president of the Thailand Development Research Institute (TDRI), he helped set the standard for evidence-based policy in Thailand and across Southeast Asia. His scholarship on rice policy, rural credit, and trade shaped debates for more than five decades; his public interventions—always clear, sometimes unsparing, and could touch on delicate political issues—made economics legible to policymakers and the public alike.